Do producer organisations promote environmental sustainability through organic soil investments? Evidence from Cameroon - Tabe-Ojong, Martin Paul Jr. (Informa UK Limited, 2023)
This study examines the relationship between cooperative membership and investments in organic soil amendments in Cameroon. We use switching regressions to reduce selection bias and estimate differential equations for both cooperative members and non-members. Cooperative membership exhibits a positive and significant relationship with the use of organic soil amendments such as farmyard manure and compost. Building on this, we further examine actual-counterfactual relationships where we find cooperative membership to be beneficial to both members and non-members should they be members. We also highlight significant heterogeneities and differential associations in the drivers and constraints of organic soil investments.